Synergistic effect of collagenase-1 (MMP1), stromelysin-1 (MMP3) and gelatinase-B (MMP9) gene polymorphisms in breast cancer - Padala, Chiranjeevi; Tupurani, Mohini Aiyengar; Puranam, Kaushik; Gantala, Srilatha; Shyamala, Nivas; Kondapalli, Mrudula Spurthi; Gundapaneni, Kishore kumar; Mudigonda, Saraswati; Galimudi, Rajesh Kumar; Kupsal, Keerthi; Nanchari, Santoshi Rani; Chavan, Uday; et al. (PloS one, 2017)
Extracellular matrix degradation by matrix metalloproteinases (MMPs) is an important mechanism involved in tumor invasion and metastasis. Genetic variations of MMPs have shown association with multiple cancers. The present study is focused to elucidate the association of MMP-1, 3 and 9 genetic variants with respect to epidemiological and clinicopathological variables by haplotype, LD, MDR, survival in silico analyses among South Indian women. MMP3-1171 5A/6A and MMP9-1562 C/T SNPs were genotyped by Allele specific polymerase chain reaction and MMP1-1607 1G/2G polymorphism by restriction fragment length polymorphism assays respectively, in 300 BC patients and age-matched 300 healthy controls. Statistical analysis was performed using the SNPStats and SPSS software. Linkage disequilibrium and gene-gene interactions were performed using Haploview and MDR software respectively. Further, transcription factor binding sites in the promoter regions of SNPs under study were carried out using AliBaba2.1 software. We have observed an increased frequency of 2G-allele of MMP1, 6A-allele of MMP3 and T-allele of MMP9 (p<0.05) respectively in BC subjects. The 2G-6A haplotype (minor alleles of MMP-1 and MMP-3 respectively) has shown an increased susceptibility to BC. Further, MMP polymorphisms were associated with the clinical characteristics of BC patients such as steroid hormone receptor status, lymph node involvement and metastasis. SNP combinations were in perfect LD in controls. MDR analysis revealed a positive interaction between the SNPs. 5-years survival rate and cox-regression analysis showed a significant association with clinicopathological variables. Our results suggest that MMP1-1607 1G/2G, MMP3-1171 5A/6A and MMP9-1562 C/T gene polymorphisms have synergistic effect on breast cancer. The interactions of MMPs clinical risk factors such as lymph node involvement has shown a strong correlation and might influence the 5-years survival rate, suggesting their potential role in the breast carcinogenesis.